Clinical profile of graft detachment and outcomes of rebubbling after Descemet stripping endothelial keratoplasty. Issue 11 (28th August 2011) - Chaurasia, Sunita; Vaddavalli, Pravin Krishna; Ramappa, Muralidhar; Garg, Prashant; Sangwan, Virender S
Abstract : Purpose: To review the clinical profile of graft detachment following Descemet's stripping endothelial keratoplasty (DSEK) and analyse the outcomes of rebubbling for graft detachment. Methods: Retrospective review. Results: 27 of a total of 309 eyes that underwent DSEK (8.7%) underwent rebubbling with air injection between January 2009 and February 2010. Eighteen (66.6%) of these eyes had complete and 9 (33.3%) had partial detachment of the transplanted lenticule. Successful attachment was observed in 20/27 (74%) eyes (12/18 with total and 8/9 with partial detachments), and clear grafts were achieved in 13 (65%) of these 20 eyes, while 7 (35%) eyes had primary graft failure. Visual acuity was 20/60 or better in 6 of these 20 eyes (35%), between 20/100 and 20/60 in 4 eyes (25%), and <20/200 in 10 eyes. Three of the 10 lenticules that failed to attach with the first rebubbling procedure underwent a second attempt of rebubbling, four underwent a repeat DSEK with good outcomes, and three underwent PK. Univariate analysis showed additional vitrectomy at the time of DSEK to be a statistically significant risk factor for persistent graft detachment following rebubbling (p<0.04). Conclusion: Rebubbling following detachment of the donor lenticule was successful in achieving graft adhesion in the majority of patients (74%), but 35% had a primary graft failure. The second attempt at rebubbling (in three patients) led to successful attachment, but the oedema failed to recover. Those who underwent repeat DSEK for unsuccessful rebubbling did well with no complications.